Regulation of stress‐induced gastric ulcers via central oxytocin and a potential mechanism through the VTA‐NAc dopamine pathway. Issue 9 (7th June 2019) - Leng, Hui; Zhang, Xiaoqian; Wang, Qian; Luan, Xiao; Sun, Xiangrong; Guo, Feifei; Gao, Shengli; Liu, Xuehuan; Xu, Luo
Abstract: Background: Oxytocin (OT) plays an important role in regulating gastric function. How OT regulates stress‐induced gastric ulcers is not understood. We investigated OT's protective role in stress‐induced gastric ulcers, with a focus on OT's interaction with the ventral tegmental area (VTA) to nucleus accumbens (NAc) dopamine pathway. Methods: Drugs administration into the rats brain nuclei by brain stereotaxic apparatus, to examine related changes in gastric ulcer index, pH of gastric content, and mucus secretion, and to determine complex interactions between OT and DA systems in the regulation of stress and gastric functions. Key Results: Neurons in the VTA were co‐immunoreactive for the OT receptor (OTR) and DA. In a rat model of stress‐induced ulcer, water‐immersion restricted stress, direct administration of OT into the VTA significantly reduced gastric ulcer index and increased the pH of gastric content and mucus secretion. OT's effects were eliminated by pretreatment with the OTR antagonist atosiban in the VTA and weakened with pretreatment of the DA D2 receptor (DA D2R) antagonist raclopride in the NAc. In OTR gene knockout (Oxtr −/− ) mice, OT's protective effect was lost. OT administered to the VTA of dorsal motor nucleus of the vagus (DMV)‐lesioned rats had minimal protective effects on gastric mucosa. Conclusions and Inferences: This study provides important data necessary for a deeper understanding of the complex interactions between OT and DA systems in the regulation of stress and gastric functions. It provides relevant mechanistic clues into OT's role as a protective factor against stress‐induced changes to gastric function. Abstract : This study provides important data necessary for a deeper understanding of the complex interactions between OT and DA systems in the regulation of stress and gastric functions. It provides relevant mechanistic clues into OT's role as a protective factor against stress‐induced changes to gastric function.